The more-than-economic dimensions of co-operation in food production - Emery, Steven; Forney, Jérémie; Wynne-Jones, Sophie (My University, 2017)
Moving forwards from an extensive literature on farmers' cooperatives, this Special Issue aims to explore the interaction and interdependence of multiple material and immaterial benefits associated with cooperation. The eight papers gathered here address a range of contexts to explore the inseparability of a set of ‘more-than-economic’ benefits of cooperation and consider the wider implications of viewing cooperation in such light. Responding to their insights, this editorial reflects upon the ontological ambiguity of concepts of economy and the political potentiality of cooperative activities. In addition, we highlight three key themes raised by the papers, which emphasize the complexity of processes and values included in cooperation: Relatedness and Embeddedness; Institutions and Formalisation; Histories and Futures. Reflecting on the transformative capacities of cooperation described in this collection, we argue that valuing cooperation as a process rather than a means to fixed-ends can carry its own emancipatory potential, given the ways in which this can work to counter the compartmentalising tendencies of capitalism. However, we conclude by cautioning that the addressing of more pervasive structural impediments needs to be integrated into cooperative endeavours if such potential is to be fully realised.
Keywords: Cooperatives Agriculture Food networks Diverse economies